1994
DOI: 10.1002/app.1994.070510208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosity ratio and processing conditions on the morphology of blends of liquid crystalline polymer and polypropylene

Abstract: SYNOPSISThe effect of viscosity ratio and processing conditions on LCP/PP blend morphology was studied. The viscosity ratio ( vLcp/vpp) was varied from 0.1 to 3.6 by using five different polypropylene grades as the matrix and two LCPs as the dispersed phase (20 wt % ). The most spontaneous fiber formation was achieved when the viscosity ratio was between 0.5 and 1. In addition to shear forces, elongational forces are important in achieving a highly fibrillar structure and significant mechanical reinforcement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 11 publications
1
59
0
Order By: Relevance
“…It was found that fiber spinning is particularly advantageous because the elongational force field in the spinning process is more effective for producing the fibrillar morphology than is the shear force field. A PP/ Nylon6 in-situ composite obtained with a spinning process has been reported in some articles [8][9] ; under spinning conditions both PP and Nylon6 can form fibers in the composite. In the present study, it was reported that PP/ Nylon6 insitu composites containing different concentration of PP and Nylon6 were obtained under an ordinary extrusion condition.…”
Section: Pp and Nylon6 Compositementioning
confidence: 98%
“…It was found that fiber spinning is particularly advantageous because the elongational force field in the spinning process is more effective for producing the fibrillar morphology than is the shear force field. A PP/ Nylon6 in-situ composite obtained with a spinning process has been reported in some articles [8][9] ; under spinning conditions both PP and Nylon6 can form fibers in the composite. In the present study, it was reported that PP/ Nylon6 insitu composites containing different concentration of PP and Nylon6 were obtained under an ordinary extrusion condition.…”
Section: Pp and Nylon6 Compositementioning
confidence: 98%
“…It has been shown that the compatibilizers consisting of a PP or PE backbone and maleic anhydride or acrylic acid grafts promote mainly specific polar interactions such a hydrogen bonds between the components [1][2][3][4][5][6][7][8] . The compatibilization mechanism of reactive compatibilizers containing epoxy groups is based on the reaction between the functional groups and the LCP end groups 9,10) .…”
Section: Characterization Of a Pe-g-lcp Compatibilizer Prepared By Rmentioning
confidence: 99%
“…These studies have shown that maleic anhydride-grafted PP (PPMA) or acrylic acid-functionalized PP (PPAA) can improve the interfacial adhesion in PP/LCP blends, and an enhancement of the tensile modulus, tensile strength, and surface finish was observed. [1][2][3][4][5][6] For blends of PE with a semiflexible LCP, compatibilized with two samples of maleic anhydride-grafted PE (PEMA), 7,8 the enhancement of the mechanical properties was generally modest. Also, in this case, the enhancement of some of the blend properties was attributed to the promotion of specific polar interactions between the components.…”
Section: Introductionmentioning
confidence: 98%
“…Recent investigations [1][2][3][4][5][6][7][8] have dealt with the preparation and the characterization of blends of polypropylene (PP) or polyethylene (PE) with liquid crystalline polymers (LCPs) containing different commercially available compatibilizers. These studies have shown that maleic anhydride-grafted PP (PPMA) or acrylic acid-functionalized PP (PPAA) can improve the interfacial adhesion in PP/LCP blends, and an enhancement of the tensile modulus, tensile strength, and surface finish was observed.…”
Section: Introductionmentioning
confidence: 99%